2019
DOI: 10.3390/ijms20112657
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Methylation-Based Detection of Urological Cancer in Urine: Overview of Biomarkers and Considerations on Biomarker Design, Source of DNA, and Detection Technologies

Abstract: Changes in DNA methylation have been causally linked with cancer and provide promising biomarkers for detection in biological fluids such as blood, urine, and saliva. The field has been fueled by genome-wide characterization of DNA methylation across cancer types as well as new technologies for sensitive detection of aberrantly methylated DNA molecules. For urological cancers, urine is in many situations the preferred “liquid biopsy” source because it contains exfoliated tumor cells and cell-free tumor DNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 108 publications
(81 reference statements)
3
68
0
Order By: Relevance
“…Indeed, it should be recalled that a relatively small number of cancer cells are exfoliated into urine, which are subsequently "diluted" among a larger population of normal-looking urothelial cells. Thus, the tumour DNA content in urine is actually minute [19] and sensitivity over 90% should be regarded as a very encouraging result. Furthermore, in the validation set, comprising a larger independent cohort, specificity of the miR663a me -VIM me multiplex panel increased to 86%, further increasing the potential usefulness of the test.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, it should be recalled that a relatively small number of cancer cells are exfoliated into urine, which are subsequently "diluted" among a larger population of normal-looking urothelial cells. Thus, the tumour DNA content in urine is actually minute [19] and sensitivity over 90% should be regarded as a very encouraging result. Furthermore, in the validation set, comprising a larger independent cohort, specificity of the miR663a me -VIM me multiplex panel increased to 86%, further increasing the potential usefulness of the test.…”
Section: Discussionmentioning
confidence: 95%
“…showed three novel gene loci, i.e., GDF15, TMEFF2, and VIM, whose DNA methylation could be suitable for detecting bladder cancers in urine samples [34]. Meanwhile, many more putative candidates have been presented [16], but most of the studies were characterized by small sample cohorts without taking into account crucial cohorts of non-malignant diseases like chronic inflammation. Hence, only a handful of biomarkers such as TMEFF2, NID2 and TWIST1 meet to some degree the needed requirements and, thus, were independently studied and validated [35].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, aberrant DNA hypermethylation of putative tumor suppressor genes emerged as a potential biomarker source for assessing early cancer detection, which has recently moved towards clinical practice, for instance, in colorectal cancer [15]. For non-invasive detection of bladder cancer, promising DNA methylation biomarkers have been described in various studies [16], but the FDA has approved none of the presented methylation biomarkers (panels) for routinely diagnostic procedures so far. In the presented study, we focused on two putative tumor suppressor genes in bladder cancer that may also hold a prognostic impact, namely inter-α-trypsin inhibitor heavy chain 5 (ITIH5) and esophageal cancer-related gene 4 (ECRG4 or C2orf40).…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic background of BlCa has been the focus of several research works. As an example, promoter methylation of several targets have been investigated in a liquid biopsy setting for proper monitoring of the disease, including in urine [34][35][36] (for further reading refer to [37]). Many studies have found several biomarkers informative for disease aggressiveness and patient outcome, including microRNAs, gene promoter methylation and specific histone modifications and chromatin alterations [38,39].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%